The effect of labor absorption, government expenditure, and life expectancy on poverty with economic growth as a mediation variable in Aceh Province - Saputra, Irfan; Syahnur, Sofyan; Silvia, Vivi (International journal of economic perspectives, 2026)
This study aims to analyze the influence of labor absorption, government expenditure, and life expectancy on poverty with economic growth as a mediating variable in Aceh Province. Panel data regression method is used. The findings in model I show that labor absorption has no effect on poverty, while government expenditure has a positive effect on poverty and life expectancy has a negative effect on poverty. Model II shows that labor absorption has a negative effect on economic growth, and government expenditure has a positive effect on economic growth while life expectancy has a positive effect on economic growth. Model III explains that economic growth has a negative effect on poverty. Model IV results in labor absorption and government expenditure have no effect on poverty, while life expectancy has a negative effect on poverty and economic growth has a positive effect on poverty. The results of the mediation effect explain that economic growth mediation has no effect on labor absorption on poverty, and government expenditure on poverty through economic growth as a mediator has a negative result, and life expectancy on poverty through economic growth as a mediator has a negative effect. Through the results of this study, it is hoped that the Aceh Government in providing poverty alleviation policies needs to be directed at synergy between increasing economic growth and improving socio-economic indicators in order to achieve community welfare.